Genetic Parameters, Correlation, and Multivariate Analysis of Yield and Yield Components in 30 Promising Wheat (Triticum aestivum L.) Genotypes - Bigyan K. C.; Rishav Pandit; Binju Maharjan; Nav Raj Adhikari; Mukti Ram Poudel; Dhruba Bahadur Thapa; Sudeep Poudel (International Journal of Agronomy)
An experiment with the aim to assess genetic variability and heritability and to examine the degree of association between yield and yield-attributing traits among the 30 wheat genotypes was performed in alpha lattice design at Golbhatta, Lalitpur. The genotypes were replicated twice with six blocks per replication and each block consisted of five genotypes. The research was carried out in farmer’s fields under irrigated conditions. The result revealed the presence of variance among different genotypes for all traits which can be exploited for improvement of the existing genotypes under irrigated conditions. Characters such as plant height, spike length, number of spikelets per spike, grain number per spike, thousand grain weight, spikes’ number per meter square, and grain yield showed higher heritability along with high genetic advance as percent of mean which are highly desirable for selection as they are governed by additive gene action. The correlation study revealed that parameters such as plant height, number of spikelets per spike, grain number per spike, and spikes’ number per meter square had positive and significant correlations with the grain yield. Among the 10 principal components, three principal components were considered on the basis of eigenvalue accounting for 75.2% of the total variation. Thirty wheat genotypes were classified into five clusters with the help of a dendrogram. Cluster 2 was found to be superior for yield and yield-attributing traits. Fifteen genotypes including two checks yielded more than the mean yield, where WK3599 (4539 kg/ha) recorded the highest yield, while WK3516 (1657 kg/ha) recorded the lowest among the genotypes. Tested genotypes revealed the presence of genetic diversity among them; hence, indirect selection of traits such as number of spikelets per spike, grain number per spike, spikes’ number per meter square and thousand grain weight will ultimately provide higher yield in these genotypes.